(3GdeWdH aj GdYed HGdQHY GdeLjHs - (3eMeO Hf eMeO Hf CMeO GdZRGd GdOeTbqj, HOQ GdOjf, GdTgjQ HSHW GdeGQOjfj , J (B912 (3g` s ((3SHW GdeGQOjfi GdTGaYi s)
(3ChdgG (B:s
(3GYde Cfg djS ai GdBdGJ Gdadcjg CTQa ef GdQHY GdeLjH dCfg jYed Hg LejY GdCYeGd ai LejY GdBaGb s
(3BNQgG (B:s
(3hdG jNai eWGdY GdZQhH heWGdY GdchGcH hjZjH hGdMeO ddg GdPi s
(3fSNI KGfjIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B357 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B1 - (3U (B97 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eYGQVI Ydi fSNI GdeDpqda (B: (3fbdJ ef NW GdeUfas
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs